Peculiarities of a Rarely Used Method of Measuring the Speech Transmission Index in Premises - Prodeus, Arkadiy; Naida, Anton; Dvornyk, Oleksandr; Didkovska, Maryna (International Journal of Architectural Engineering Technology, 2023)
Evaluation of speech transmission index (STI) in premises allows for determining the speech intelligibility, and therefore the suitability of premises for speech communication. STI measurements using the speech transmission index for telecommunication systems (STITEL) method are rarely performed in rooms, possibly due to insufficient information on the accuracy of this method. In this paper, computer simulations were used to estimate the STI estimation errors by the STITEL method under conditions of noise and reverberation. The pink noise model and the room impulse response estimate of a real room with a reverberation time T60=0.8 s were used for the research. The duration of the test signals varied between 4, 8, 16, 32, and 64 seconds, and the signal-to-noise ratio varied from minus 28 dB to plus 28 dB. The dependences of the bias, standard deviation, and total error of the STI estimate on the duration of the test signal and the signal-to-noise ratio are obtained. It is shown that the total error of the STI estimation is close to 0.03 when the duration of the test signal is 8 s. Under conditions of noise action, this error decreases with a further increase in the duration of the test signal. Under conditions of joint action of noise and reverberation, such a decrease was not observed, while the total error is within 0.03-0.04.